Kebijakan Kepala Sekolah Dalam Meningkatkan Disiplin Kerja Tenaga Kependidikan di SMKN 1 Batusangkar - Monadia Turrahmi Zulkifli (STKIP PGRI SITUBONDO, 2023)
The main problem in this study is that there are some training faculty who actually abuse the school rules, for example, arrive later than expected, leave early and there are also teaching staff who seek work elsewhere for their own benefit, it can be said that almost every day there are teaching staff who appear after the expected time, in completing the work requested by the leadership in accordance with their obligations and their abilities are still not ideal at work. the principal of SMKN 1 Batusangkar plays seven parts in further developing the work discipline of the training staff, in particular: the school principal educator provides opportunities and applies strictly to instructive staff. As well as giving directions to instructive staff who abuse standards. As a manager the principal manages his subordinates with the aim that they can work together so as to create more work discipline. As an administrator the principal has a pleasurable connection with different administrative organization practices such as record keeping, ordering and detailing, as a supervisor especially leads supervision and control to further develop work discipline throughout the family. As a pioneer, the principal coordinates, motivates, empowers, and coordinates all meetings related to achieving school goals, and has the choice to acknowledge the analysis and ideas of his subordinates. As innovators, principals direct, develop, empower, and coordinate all meetings related to achieving school goals, and have the option to acknowledge analysis and ideas from their subordinates. And as a motivator complete various exercises that can give energy to work, and include instructive staff in every movement. The research used is field research which is a subjective description. The information gathering procedure used is through perceptions, meetings, moreover, documentation. The validity of the data used is triangulation. The insightful procedure used by Miles and Huberman.